Design and Thermodynamic Modeling of a Recuperative ORC Binary System for Double Flasher Geothermal Power Plant - Alif Addamaghany Kurniawan; Roby Pratama Sitepu; Timotius Dimas Narendra Basoeki; Irham Isa Maulana; Ali Zainal Abidin; Avatar Sargamantha Ndoen; Muhammad Husni Mubarok (Mesin, 2026)
This research evaluates the thermodynamic performance of a recuperative binary Organic Rankine Cycle (ORC) integrated with a double-flash geothermal power plant, modeled using Aspen HYSYS for medium-enthalpy resources (200°C) common in Indonesia, such as Lahendong or Wayang Windu fields. Configurations compared include standalone double-flash (baseline), double-flash + simple ORC, and double-flash + recuperative ORC, with n-pentane selected as the optimal working fluid for its superior net power output, thermal efficiency, and low specific investment cost among alternatives like isopentane and isobutane. Fixed geothermal brine inputs (180°C, 15 bar, ~144-146 kg/s) simulate real Indonesian conditions. Results demonstrate the recuperative design's superiority: ORC efficiency rises by ~2% (13.71% vs. 11.71%), overall plant efficiency by 3.26% (21.5% vs. 18.24%), and net power output by 168% (5229 kW vs. 1514.6 kW baseline), driven by recuperator-enabled heat recovery that cuts evaporator duty by 15-25% and condenser rejection. Geothermal segment efficiency improves to 5.62% from 4.55%. Recuperator design features shell-and-tube units (e.g., 5181 mm tube length, 2100 mm shell diameter, U=65 W/m²K, area ~1889 m²) with minimal pressure drops. Findings align with global benchmarks (e.g., 3-4% efficiency gains, 35% power boosts) and support Indonesia's 40 GW geothermal potential via modular ORC for brine utilization. Recommendations emphasize economic optimization and scaling for Lahendong expansions.